Research and design of the intelligent energy management and control platform in the airport area based on the IoT technology - Yuan HUANG; Gang WU; Junyong LIU; Chenxi YANG; Mengpin GAO (物联网学报)
The construction of the green airport urgently needs an efficient energy security information system in face of the electric energy substitution and clean energy access.A design idea of the intelligent energy management and control platform in the airport area based on the Internet of things (IoT) technology was proposed.The platform included a perception layer, a network layer, a data layer and an application layer.The IoT technology and the fusion technology of the information and energy were adopted to realize the application scenarios for multiple users.Finally, an energy control platform framework was designed by combing the energy information of a civil hub airport to provide basic services for further exploration of the value of the energy.